Stylistic Shifts in The Paintings of the Artist Muhammad Aref :Technical Analytical Study - Twana Yahya Khader; Qasim Hussain Saleh; Moaid Ismail Jarjis (Zanco Journal of Humanity Sciences)
The research project "The stylistic transformations in the paintings of the artist Muhammad Arif" is an artistic and analytical study consisting of four chapters. The second chapter is dedicated to the theoretical framework and includes two sections: the first topic, the concept of the constant and the variable, and the second topic, style and stylistics in modern drawing, followed by the selection of indicators for the theoretical framework and previous studies. The third chapter is concerned with research procedures. It consists of the research community, the research sample, and the research methodology, which includes three samples. As for the fourth and final chapter, it deals with the results and conclusions of the research. The results were: 1. Muhammad Arif expressed his feelings and emotions in an expressive manner, ignoring the details to express what was inside the artist himself, as in a sample (1). 2. He also used symbolism to express his ideas through the use of realistic forms, as in example (2), and politics within its subject, as shown in sample (3). 4. The artist was inspired by the surrounding geographical environment to use natural elements as in the sample (1-2-3). 5. Muhammad Arif dealt with the political and social content whose influence stemmed from the surrounding environment, and this was evident in a sample (1-2-3). The researchers presented some recommendations and suggestions, and finally a list of sources.